Phosphorylation of SOS3-Like Calcium-Binding Proteins by Their Interacting SOS2-Like Protein Kinases Is a Common Regulatory Mechanism in Arabidopsis(1)([W])([OA]) - Du, Wenming (American Society of Plant Biologists, 2011)
The Arabidopsis (Arabidopsis thaliana) genome encodes nine Salt Overly Sensitive3 (SOS3)-like calcium-binding proteins (SCaBPs; also named calcineurin B-like protein [CBL]) and 24 SOS2-like protein kinases (PKSs; also named as CBL-interacting protein kinases [CIPKs]). A general regulatory mechanism between these two families is that SCaBP calcium sensors activate PKS kinases by interacting with their FISL motif. In this study, we demonstrated that phosphorylation of SCaBPs by their functional interacting PKSs is another common regulatory mechanism. The phosphorylation site serine-216 at the C terminus of SCaBP1 by PKS24 was identified by liquid chromatography-quadrupole mass spectrometry analysis. This serine residue is conserved within the PFPF motif at the C terminus of SCaBP proteins. Phosphorylation of this site of SCaBP8 by SOS2 has been determined previously. We further showed that CIPK23/PKS17 phosphorylated CBL1/SCaBP5 and CBL9/SCaBP7 and PKS5 phosphorylated SCaBP1 at the same site in vitro and in vivo. Furthermore, the phosphorylation stabilized the interaction between SCaBP and PKS proteins. This tight interaction neutralized the inhibitory effect of PKS5 on plasma membrane H(+)-ATPase activity. These data indicate that SCaBP phosphorylation by their interacting PKS kinases is a critical component of the SCaBP-PKS regulatory pathway in Arabidopsis.